Using Univariate Bezier Distributions to Model Simulation Input Processes - Flanigan Wagner, M.A.; Wilson, J.R. (WSC, '93: Winter Simulation Conference Proceedings, 1993)
In this paper we describe a graphical, interactive technique for modeling univariate simulation input processes with a distribution family based on Bezier curves. This family has an open-ended parameterization and is capable of accurately representing an unlimited variety of distributional shapes. Our input-modeling technique is implemented in a self-contained, Windows-based software system called PRIME-PRobabilistic Input Modeling Environment. Several examples illustrate the application of this technique.